Distributions of particulate and dissolved phosphorus in aquatic habitats of Peninsular Malaysia. (March 2018) - Lim, Joon Hai; Lee, Choon Weng; Bong, Chui Wei; Affendi, Yang Amri; Hii, Yii Siang; Kudo, Isao
Abstract: Particulate phosphorus was the dominant phosphorus species and accounted for 72 ± 5% of total phosphorus in coastal habitats, 63 ± 4% in estuaries, 58 ± 6% in lakes and 80 ± 7% in aquaculture farms whereas dissolved inorganic phosphorus (DIP) and dissolved organic phosphorus (DOP) were minor components. Correlation analyses (DIP vs Chl a ; R 2  = 0.407, df = 31, p < 0.001) suggested phosphorus limiting conditions in lakes, which was corroborated with the highest alkaline phosphatase activity (APA) that fluctuated from 0.38 to 41.14 nmol L −1  min −1 . In contrast, APA was elevated in coastal habitats and estuaries only when DIP concentration decreased below 0.9 μM. Moreover size-fractionation experiment showed that the highest APA was detected in the 0.2–2 μm pico-size fraction. Our results suggested that the main APA in coastal habitats and estuaries was from phototrophic pico-eukaryotes and heterotrophic bacteria, and regulated largely by DIP availability. Highlights: Long-term observation showed deteriorating trophic states. Most alkaline phosphatase activity (APA) in coastal habitat was from picoplankton. APA in coastal habitat was regulated by dissolved inorganic phosphorus. APA was induced when dissolved inorganic phosphorus decreased <0.9 μM.